Coaching: An Effective Approach to Facilitate Performance, Learning and Advancement of Medical Students - Fariba Asgari; Hojjat Houshyari khah; Marzieh Shayestehfard (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Dear Editor The challenging conditions of today's world and the rapid advancement in various sciences have prompted higher education institutions to update their teaching and learning approaches. This improvement aims to support learners in enhancing their capabilities and achieving effective performance in the current complex environment, enabling them to act as agents of change and respond to social and organizational needs (1). Medical education institutions must also invest in developing successful clinical learning models that align with real-world challenges, equipping students with the skills and attitudes necessary for lifelong learning and continuous professional development. The coaching approach, which has gained momentum in medical education since 2000, particularly in recent years, can play a significant role in this regard (2, 3). In clinical education, coaching serves as a supportive approach for learners aiming to maximize their potential through goal setting (4). This method is grounded in one-on-one dialogue, which includes verbal questioning and feedback between the coach and the student within the clinical learning environment (1). While various models exist for implementing this approach, the GROW model is regarded as the most suitable for training students. Participation in this model typically begins before the introductory session, where the coach explains the concept of coaching, outlines expected outcomes and establishes clear, measurable goals. During the reality stage, the coach poses questions to the learner about their progress toward goals and the obstacles they encounter, fostering greater self-awareness. The coach then assists the learner in creatively exploring strategies to achieve their objectives. In the final stage, the student and coach agree on specific actions to be taken within a designated timeframe and clarify the learner's level of commitment and accountability (5). To further enhance the supportive aspect of this approach, additional resources and strategies, such as educational supervisors, study guides, or workshops based on real-case scenarios, can also be utilized (6). Given the nature of the coaching process, it is clear that this approach underpins a philosophy of learning that encourages students to take responsibility for their own learning and engage in learner-centered exploration. This is achieved by setting learner-centered goals, selecting strategies to reach these goals, and self-assessing their learning. In this framework, coaches typically position themselves as supportive guides, encouraging students to question and explore (7). While the coaching process thrives on interactions built on trust and respect, the responsibility for making changes ultimately rests with the learner and the coach assuming a supervisory role. The coach employs active listening techniques and open-ended questions to assist in goal setting and establish pathways toward achieving them, empowering the learner in the process (4). Moreover, coaching creates experiential learning opportunities, as coaches design meaningful learning experiences derived from clinical situations that incorporate reflection and feedback (7). Throughout this dialogue, coaches closely observe and evaluate the student's performance in clinical settings, encouraging them to reflect on their practice methods. By asking analytical questions and providing constructive feedback, coaches challenge students to identify their concerns and areas for improvement. These ongoing, purposeful interactions between the coach and learner enhance the students' critical thinking and clinical reasoning skills, helping to bridge the gap between theory and practice (2). Based on this, coaching is an educational approach with the potential to create an environment that supports students in achieving their educational goals and advancing in clinical settings. This approach can be particularly effective in medical education. Given the emerging nature of coaching in this field and the limited existing research, further studies are needed to explore coaching in healthcare professions, as well as to develop and evaluate interventions related to coaching in clinical performance.